2022
DOI: 10.3389/fmed.2022.948025
|View full text |Cite
|
Sign up to set email alerts
|

Case report: COVID-19 infection in a pregnant 33-year-old kidney transplant recipient

Abstract: Patients facing severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) infections with comorbidities, especially patients whose immune system is weakened have higher chances to face severe outcomes. One of the main reasons behind the suppression of the immune system is iatrogenic, in patients who have autoimmune diseases and/or had an organ transplant. Although there are studies that are examining immunocompromised and/or transplanted patients with COVID-19 infection, furthermore there is a limited numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…NLR was studied in pregnant COVID-19 patients as well ( 74 , 75 ): Aydin Güzey et al ( 76 ) evaluated 254 cesarean sections with COVID-19 and found elevated levels of NLR among the symptomatic patients. Our research group also presented a case report where we found elevated NLR in a preeclamptic COVID-19 patient ( 77 ). Our research group additionally conducted a case–control study, which included 45 pregnant patients with COVID-19.…”
Section: Commentmentioning
confidence: 83%
“…NLR was studied in pregnant COVID-19 patients as well ( 74 , 75 ): Aydin Güzey et al ( 76 ) evaluated 254 cesarean sections with COVID-19 and found elevated levels of NLR among the symptomatic patients. Our research group also presented a case report where we found elevated NLR in a preeclamptic COVID-19 patient ( 77 ). Our research group additionally conducted a case–control study, which included 45 pregnant patients with COVID-19.…”
Section: Commentmentioning
confidence: 83%
“…Our research group previously reported the case of a 33-year-old pregnant kidney transplant recipient patient. During her COVID-19 illness, her NLR values were elevated, she required non-invasive respiratory support, and she exhibited pre-eclamptic symptoms [34]. After reporting this interesting case, our focus shifted to researching NLRs in pregnant COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%